Rewriting Culture Through Rewriting Myths and Legends: a Study of Rashmi Bajaj’S Nirbhay Ho Jao Draupadi: Rewriting the Cultural Landscape: Rashmi Bajaj's Feminist Exploration in Nirbhay Ho Jao Draupadi (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Indian  women writers  have  obtained critical  praise  for their  brilliant  literary skill  and  making social  issues  a key  part  of their  work. Indian  women authors  writing  in English  such  as Kiran  Desai  and Arundhati  Roy  have earned  international  renown. But a  number  of Indian  women  writing in  regional  languages such  as  Hindi, Tamil, Bengali, Malayalam  and Kannada  have  gained wider  recognition  due to  a  strong and  growing  market for  quality  Indian fiction  in  translation. “Regional  language literature  has  always been  a  vast reservoir  of  wealth waiting  to  be explored  and  no matter  how  much of  it  is translated  into  English; only the  tip  of the  iceberg  emerges. Hindi  writing, in particular, holds  an  embarrassment of  riches  that is  just  begging to  be  tapped.” (Basu  6) In the  multitude  of such  Hindi  writings, Rashmi  Bajaj – a bilingual  poet  and writer  in  Hindi and  English, stands  out with  her  poetry collection  Nirbhay  Ho  Jao Draupadi for  its  amalgamation of  fierce  sarcastic articulation  of  feminism and  silky  serenity of  persoanl  voice. She is  dissatisfied  with the  given  world and  wishes  to transform  it  by redesigning  the  very cultural  construction  which forces  a  human to  become  woman.